2011
DOI: 10.1371/journal.pone.0024609
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer Related Gene-4 Is a Choroid Plexus-Derived Injury Response Gene: Evidence for a Biphasic Response in Early and Late Brain Injury

Abstract: By virtue of its ability to regulate the composition of cerebrospinal fluid (CSF), the choroid plexus (CP) is ideally suited to instigate a rapid response to traumatic brain injury (TBI) by producing growth regulatory proteins. For example, Esophageal Cancer Related Gene-4 (Ecrg4) is a tumor suppressor gene that encodes a hormone-like peptide called augurin that is present in large concentrations in CP epithelia (CPe). Because augurin is thought to regulate senescence, neuroprogenitor cell growth and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 36 publications
4
74
0
Order By: Relevance
“…Likewise, we performed qRT-PCR and demonstrated elevated ECRG4 lung expression (lane 1) in comparison to heart (lane 2) and skin (lane 3) (Figure 1B). Immunoblotting of mouse lung with the anti-ECRG4 antibody [27, 46] revealed the presence of a single 14 kDa peptide that corresponded to the molecular weight of the predicted precursor product, amino acids 31–148, of ECRG4 (Figure 1C). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, we performed qRT-PCR and demonstrated elevated ECRG4 lung expression (lane 1) in comparison to heart (lane 2) and skin (lane 3) (Figure 1B). Immunoblotting of mouse lung with the anti-ECRG4 antibody [27, 46] revealed the presence of a single 14 kDa peptide that corresponded to the molecular weight of the predicted precursor product, amino acids 31–148, of ECRG4 (Figure 1C). …”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies suggest that ECRG4 plays a role in injury homeostasis because its downregulation after injury/inflammation allows for dysinhibition of cell proliferation in vivo [27, 29, 46, 50, 51]. Its epigenetic regulation, however, suggests that the return of basal gene expression after injury could depend on epigenetic factors determined by environment, diet, and age.…”
Section: Introductionmentioning
confidence: 99%
“…The C2ORF40 gene is important in processes associated with physiological functional regulation, including inflammation, injury, senescence, the neuroendocrines environment, differentiation and apoptosis (5)(6)(7)(8)(9)(10)(11)(12)(13). Notably, previous studies have indicated that C2ORF40 is a candidate tumor suppressor gene associated with prognosis in a variety of tumors (4,(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on the potential for esophageal cancer related gene-4 (ECRG4) to serve as a sentinel factor on immune cells that may regulate the immune set point based on its expression on the surface of leukocytes, its release from the cell surface after inflammatory stimuli, and its epigenetic regulation that may explain differences in Ecrg4 expression between individuals [6][7][8][9]. Esophageal cancer related gene-4 encodes a 148 amino acid precursor protein that is tethered to the cell surface but shed on activation [6,10].…”
mentioning
confidence: 99%
“…Esophageal cancer related gene-4 encodes a 148 amino acid precursor protein that is tethered to the cell surface but shed on activation [6,10]. We have demonstrated previously that ECRG4 is present on the surface of polymorphonuclear leukocytes (PMNs) and, on ex vivo activation by agonists such as lipopolysaccharide (LPS), ECRG4 is released and can be detected by immunoblotting and proteomic analyses of biologic fluids including conditioned media, cerebrospinal fluid, and serum [6,7,[10][11][12]. We have also demonstrated that ECRG4 interacts with the human innate immunity receptor complex (TLR4-CD14-MD2) supporting further an important role in responding to inflammatory insults such as severe injury [13].…”
mentioning
confidence: 99%